How to overcome cardiovascular challenges in COVID-19 patients: a guide for common practice - Eslami, Pegah; Tabary, Mohammadreza; Dooghaie-Moghadam, Arash; Khaheshi, Isa (Acta Biomedica Atenei Parmensis, 2020)
The COVID-19 epidemic initially started in Wuhan, China in December 2019 due to SARS-CoV-2. SARS-CoV-2 is genetically similar to the bat beta-coronavirus genus, but the novel specie of this genus can infect humans. The most common clinical features of COVID-19 are fever, cough, myalgia, fatigue, expectoration, and dyspnea. The primary reported mortality rate was about 2-3% in China; however, it reached up to 10% among patients with underlying cardiovascular diseases. The primary epidemiological investigations showed a high prevalence of underlying cardiovascular diseases in more than 40% of infected patients. A high prevalence of hypertension, ischemic heart disease, and diabetes were reported among deceased patients in Italy. Previous experiments in different pandemic situations showed that the cardiovascular system has been affected in many ways. Previous studies on SARS-CoV and MERS-CoV reported that cardiovascular co-morbidities had a direct correlation with the risk of infection, the severity of disease, and the mortality rate. Therefore, brief and available protocols for controlling the negative effects of this novel respiratory infection on the cardiovascular system, especially in a high-risk populations with underlying cardiovascular conditions, is one of the most serious concerns among healthcare providers. Herein, we aimed to review the available data on the cardiac manifestation of COVID-19. Besides, we described useful maps for the better treatment of COVID-19 infection in patients with underlying cardiovascular conditions, as a high-risk group of patients.